O Yoga do eterno retorno: tempo e eternidade na tradição do Yoga clássico - Tomaz Pedrosa de Tassis (2018)
This dissertation aims to study the Sanskrit philosophical texts of '' Classical Yoga '', also collectively called Pātañjala Yogaśāstra. The basic text consists of Yoga Sūtras and the commentary entitled Yoga Sūtra Bhāṣya, attributed by tradition to Patañjali and Vyāsa, respectively. The first objective is the exposition of the yogic doctrines about time, its relation to ascetic practices and its eventual overcoming through the techniques of introverted concentration (samādhi). To this end, we adopt the theoretical perspectives present in the works of Mircea Eliade and Georg Feuerstein, who seek to emphasize the mythological and religious elements in the text of Yoga Sūtras. The mythical foundations and the relationship established between the texts of Classical Yoga and the puranic cosmologies that underlie them, the Buddhist, Upanishadic, and Sāṃkhya elements will be unraveled in order to more explicitly explain the yogic doctrines about the nature of the cosmos, meditation, and of transformation processes inherent in phenomenal reality. Our exposition will result in a comparison between the foundations of the ontology exposed in Pātañjala Yogaśāstra and the concept of "archaic ontology", derived from the work of Mircea Eliade.